2020
DOI: 10.3390/fi12090141
|View full text |Cite
|
Sign up to set email alerts
|

A Distributed Architecture for Smart Recycling Using Machine Learning

Abstract: Recycling is vital for a sustainable and clean environment. Developed and developing countries are both facing the problem of solid management waste and recycling issues. Waste classification is a good solution to separate the waste from the recycle materials. In this work, we propose a cloud based classification algorithm for automated machines in recycling factories using machine learning. We trained an efficient MobileNet model, able to classify five different types of waste. The inference can be performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Ziouzios et al [8] proposed a cloud based classification approach for automatic machines in recycling factories with ML algorithm. They trained an effective MobileNet method, capable of classifying 5 distinct kinds of waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ziouzios et al [8] proposed a cloud based classification approach for automatic machines in recycling factories with ML algorithm. They trained an effective MobileNet method, capable of classifying 5 distinct kinds of waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have shown that the consumption of products is a crucial factor in the amount of SWM (Bosire et al, 2017). The challenges in the SWM is correlated environmental effect and also economic impacts on the world (Ziouzios et al, 2020). Around the planet, solid waste contributes to climate change and is one of the leading causes of carbon emissions.…”
Section: Machine Learning Approaches In Swmmentioning
confidence: 99%
“…• Edge devices and fog nodes support performing analytics; however, dedicated hardware needs to be designed and developed with high computational power for performing the AI models (Zou et al, 2019). However, with recent advancements, low power machine learning processors are embedding in the local server, gateways, and routers.…”
Section: Future Directionsmentioning
confidence: 99%
“…Smart waste sorting can be achieved using an object detection model and by engaging the householders using machine learning-based gamification recycling applications [2,5]. Further, a cloud-based smart waste segregation architecture can be built using an object detection model to sort recyclable waste [3]. The ability of Convolution Neural Networks (CNNs) to provide reliable accuracy, learn new unique and abstract features shows promise in the domain of computer vision [10,11,12].…”
Section: Related Workmentioning
confidence: 99%
“…Recycling centers use mechanical and chemical technology for plastic waste sorting. Current research is focusing on image-based smart waste recycling [1,2,3,4,5]. Plastic waste is sorted into its individual types namely, Polyethylene Terephthalate (PET), High-Density Polyethylene (HDPE), Polypropylene (PP), Polystyrene (PS), Polyvinyl Chloride (PVC), and Low-Density Polyethylene (LDPE).…”
Section: Introductionmentioning
confidence: 99%